Ascorbic acid assisted synthesis of rGO-TIO2 hydrogel nanocomposite for methylene blue degradation - Tee, Chee Yin (2019)
Photocatalysis reaction has been widely used in the degradation of cationic dyes. But, only TiO2 are less effective in the photocatalytic reaction. With the addition of carbon compound, such as graphene and its oxides, the nanocomposite could perform more efficiently in the removal of cationic dyes such as methylene blue. The construction of reduced graphene oxide (rGO) had gained more and more attention due to its high electronic properties especially in semiconductor industries. The non-localised electron could help in fast transform of energy. In this study, the main objective was to synthesis and characterised the rGO-TiO2 nanocomposite as well as the photocatalytic reaction of rGO-TiO2 nanocomposite towards methylene blue degradation. In this contribution, rGO was synthesised by simplified Hummer’s method and then continued by the synthesis of rGO-TiO2 nanocomposite via hydrothermal reaction with assisted of ascorbic acid as reducing agent. The synthesised rGO-TiO2 nanocomposite was characterised by Scanning Electron Microscope (SEM), Field Emission-Scanning Electron Microscope (FE-SEM), X-Ray Diffraction (XRD), UV-Vis spectroscopy, and the Fourier Transform Infrared Spectroscopy (FTIR). With the present of rGO, the photocatalytic degradation of methylene blue under natural UV light irradiation were markedly improved. The results revealed that different ratio of rGO : TiO2 has substantial influence on the photocatalytic degradation of methylene blue under UV light irradiation. The rGO-TiO2 nanocomposite with highest ratio, which is 1:0.15 had the best photocatalytic reaction towards methylene blue degradation.